A proposed methodology for understanding urban growth pattern : a case study in Siem Reap, Cambodia - Ourng, Chanvoleak (2011)
In this paper, the main goal is to understand the relationship between urban growth and physical factors in order to determine the potential area for future urban expansion. A methodology is suggested for understanding urban growth pattern in Siem Reap which could effectively sustain archaeological sites and to balance the land use between urban and non-urban areas in Siem Reap, Cambodia. Remote sensing technique is used to analyze land use maps of Siem Reap from 1993 to 2011. Results show that urban-built up area increased significantly which causes the forest land to reduce steadily from 1993 to 2003 in the Siem Reap archaeological sites. In addition, Geographic Information System (GIS) is applied to analyze urban growth pattern. Geo-processing and logical functions are applied to detect and quantify the land use changes, especially urban changes. Two main factors are used to analyze the urban driving growth in Siem Reap, which are distance to road networks and population density. Pearson correlation statistics is applied to justify the relationship between the factors and urban area growth.